The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1155/2010/529359
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effect of Cinnamaldehyde on Monocyte/Macrophage-Mediated Inflammatory Responses

Abstract: Cinnamaldehyde (CA) has been known to exhibit anti-inflammatory and anticancer effects. Although numerous pharmacological effects have been demonstrated, regulatory effect of CA on the functional activation of monocytes and macrophages has not been fully elucidated yet. To evaluate its monocyte/macrophage-mediated immune responses, macrophages activated by lipopolysaccharide (LPS), and monocytes treated with proaggregative antibodies, and extracellular matrix protein fibronectin were employed. CA was able to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 32 publications
2
48
0
2
Order By: Relevance
“…In addition, we found that CA treatment suppresses tumor growth in mice and vessel formation in tumors. CA reduced HIF-1a and VEGF expression in cancer cells, and it has been reported to have antioxidant and anti-inflammatory actions [19][20][21][51][52][53]. These collective findings suggest that CA could be an effective cancer therapeutic agent through its orchestrated actions on apoptosis and angiogenesis in cancer and vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, we found that CA treatment suppresses tumor growth in mice and vessel formation in tumors. CA reduced HIF-1a and VEGF expression in cancer cells, and it has been reported to have antioxidant and anti-inflammatory actions [19][20][21][51][52][53]. These collective findings suggest that CA could be an effective cancer therapeutic agent through its orchestrated actions on apoptosis and angiogenesis in cancer and vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 76%
“…CA has been shown to have antioxidant, anti-microbial, and anti-diabetic effects [17][18][19]. Moreover, it has been reported to have chemopreventive activities against several tumors and anticancer functions by inhibiting proliferation and inducing apoptosis [20,21]. However, a role for CA in angiogenic regulation has not yet been defined.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory effects of cinnamon water extract on phosphorylation of ERK1/2 and scavenger activity in macrophage has been revealed [26]. Cinnamaldehyde, the major constituents of Cinnamomi cortex [27], possesses versatile biological activities [17,18,[33][34][35]. In macrophage, cinnamaldehyde suppressed the production of pro-inflammatory mediators such as COX-2 and iNOS through attenuation of activation of ERK1/2, p38 and NF-κB [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Cinnamaldehyde, the major constituents of Cinnamomi cortex [27], possesses versatile biological activities [17,18,[33][34][35]. In macrophage, cinnamaldehyde suppressed the production of pro-inflammatory mediators such as COX-2 and iNOS through attenuation of activation of ERK1/2, p38 and NF-κB [33,34]. In addition, cinnamaldehyde inhibited activation of signaling pathway related with allergic inflammation in RBL-2H3 cells and mBMMCs [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] As cinnamaldehyde showed the anti-inflammatory effect in macrophages, we speculated that TCA may exhibit a similar anti-inflammatory effect in microglia, which act as a sensor for pathological events in the central nervous system (CNS). 17,18) Therefore, we evaluated the effects of TCA on lipopolysaccharide (LPS)-induced nitric oxide (NO) release and the expressions of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in the BV2 microglial cells. We further investigated the neuroprotective efficacy of TCA on dopaminergic degeneration and its suppressive effects on the increased iNOS and COX-2 expressions, which were induced by a 6-hydroxydopamine (6-OHDA) injection to mice.…”
mentioning
confidence: 99%